Mechanisms of Polarized Organelle Distribution in Neurons - Britt, Dylan J.; Farías, Ginny G.; Guardia, Carlos M.; Bonifacino, Juan S. (Frontiers in Cellular Neuroscience, 2016)
Neurons are highly polarized cells exhibiting axonal and somatodendritic domains with distinct complements of cytoplasmic organelles. Although some organelles are widely distributed throughout the neuronal cytoplasm, others are segregated to either the axonal or somatodendritic domains. Recent findings show that organelle segregation is largely established at a pre-axonal-exclusion zone (PAEZ) within the axon hillock. Polarized sorting of cytoplasmic organelles at the PAEZ is proposed to depend mainly on their selective association with different microtubule motors and, in turn, with distinct microtubule arrays. Somatodendritic organelles that escape sorting at the PAEZ can be subsequently retrieved at the axon initial segment (AIS) by a microtubule- and/or actin-based mechanism. Dynamic sorting along the PAEZ-AIS continuum can thus explain the polarized distribution of cytoplasmic organelles between the axonal and somatodendritic domains.